2011
DOI: 10.1111/j.1365-2621.2010.02512.x
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition and fatty acid profile of three different fresh and dried commercial sea cucumbers from Turkey

Abstract: Proximate composition and fatty acid (FA) profile of three commercial sea cucumbers; Holothuria tubulosa, Holothuria polii and Holothuria mammata caught from Aegean Sea of Turkey were analysed. The effects of regional variation and drying process on FA composition were also investigated. Moisture, protein, fat and ash contents of the species ranged between 81.24% and 85.24%, 7.88% and 8.82%, 0.09% and 0.18%, and 5.13% and 7.85%, respectively, with a significant changes among species (P < 0.05) with some except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
84
6
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 32 publications
19
84
6
4
Order By: Relevance
“…This finding was supported by Svetashev et al [22] who pointed out that the major fatty acids discovered in almost all species of sea cucumber was arachidonic acid while the total PUFA were higher than total SFA and MUFA [23]. The results obtained supported previous studies.…”
Section: Discussionsupporting
confidence: 83%
“…This finding was supported by Svetashev et al [22] who pointed out that the major fatty acids discovered in almost all species of sea cucumber was arachidonic acid while the total PUFA were higher than total SFA and MUFA [23]. The results obtained supported previous studies.…”
Section: Discussionsupporting
confidence: 83%
“…Normally the moisture content in most of the sea cucumbers were in the range of 84% to 91% [24], 83% to 86% in Isostichopus sp [34], 81% to 85% for H. tubulusa [9], even higher than present study as reported 89% to 90% in Parastichopus sp [35] and 87% to 90% in Cucumaria frondosa [31]. Moisture percentages in various studies can be link to due to collection time of year, environmental factors, geographical variations and feeding behaviour of respective species [35].…”
Section: Proximate Compositionscontrasting
confidence: 41%
“…Poly Unsaturated Fatty Acids (PUFA) were the primary fatty acid in sea cucumber of which Eicosapentaenoic acid (EPA) [7] arachidonic acid (ARA) [8], docosaheaxanoic acid (DHA) [9] are the dominant fatty acids being reported across various studies. Mono Unsaturated Fatty Acids (MUFA) were detected in the body wall of sea cucumber [6] of which Palmitoleic acid detected as anti-inflammatory effect, anorexic and mitigation on type 2 diabetes [10] and also has potentiality for curing obesity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive compounds found in marine organisms, such as seaweeds, soft corals, sponges, mollusks, phytoplanktons, tunicates, echinoderms, and bacteria have shown wide variety of applications in medicinal fields (19,20). Holothurians have been used for centuries as an anti-inflammatory and antidisease food source and for treating different ailments in South East Asian countries, such as Korea, Japan, Indonesia, and China (21,22). They are nutrient-rich invertebrates, similar to cucumber with a leathery skin and gelatinous body (23).…”
Section: Discussionmentioning
confidence: 99%